OLE-remote automation Visual Basic 4 - Spencer, Kenneth L. 1951- (Prentice Hall PTR, 1996)
Microsoft Visual Basic 4.0 is the first development environment to support OLE-Remote Automation. Now, this handbook explains this new technology and how it is implemented in Visual Basic 4.0. Users walk through the application development process as they create, test, and debug sample applications. Programming examples and sample applications are included on the disk.